Prevalence of alexithymia in patients with psoriasis and its association with disease burden: a multicentre observational study. (10th April 2017) - Sampogna, F.; Puig, L.; Spuls, P.; Girolomoni, G.; Radtke, M.A.; Kirby, B.; Brunori, M.; Bergmans, P.; Smirnov, P.; Rundle, J.; Lavie, F.; Paul, C.; et al.
Summary: Background: Single‐centre studies show that alexithymia, defined as difficulty in recognizing and describing emotions, is more prevalent among patients with psoriasis than in the general population. However, its prevalence and the consequences of the association between alexithymia and psoriasis are unclear. Objectives: The primary objective of this study was to determine the prevalence of alexithymia, as defined by a score ≥ 61 in the 20‐item Toronto Alexithymia Scale, in a large sample of patients who had plaque psoriasis for ≤ 10 years and were eligible for phototherapy or systemic treatment. The secondary objectives were to investigate the relationship between alexithymia and the clinical and psychological aspects of psoriasis. Methods: Data were collected in the framework of an observational, multicentre, international study, the EPidemiological Study In Patients With Recently DiagnosEd PSOriasis (EPIDEPSO), aiming at investigating the prevalence of alexithymia and other psychosocial comorbidities in patients with psoriasis of ≤ 10 years' disease duration. Results: The prevalence of alexithymia within a cohort of 670 patients was 24·8% (95% confidence interval 21·7–28·2). Patients with alexithymia had a higher burden of psoriasis, including significant impairment of quality of life, higher levels of anxiety and depression, a higher risk of alcohol dependency and impairment of work productivity, compared with patients without alexithymia. Conclusions: It is important to identify alexithymic patients with psoriasis in clinical practice as they experience a higher disease burden and have a lower ability to express their feelings. Abstract : What's already known about this topic? Psoriasis is associated with psychological comorbidities. Alexithymia, defined as difficulty in recognizing and describing one's emotions, has been associated with psoriasis in single‐centre studies. What does this study add? In this large multicentre study, around 25% of patients with psoriasis had alexithymia. Patients with alexithymia experienced significant impairment to quality of life, higher levels of anxiety and depression, a higher risk of alcohol dependency, and impairment of work productivity. What are the clinical implications of this work? Special attention should be given to alexithymic patients with psoriasis when discussing treatment modalities, as they are unable to express their emotions appropriately and communicate satisfactorily with the practitioner. Respond to this article